2021
DOI: 10.1038/s41598-021-97548-1
|View full text |Cite
|
Sign up to set email alerts
|

Altered fecal microbiota composition in individuals who abuse methamphetamine

Abstract: As a severe public health problem, methamphetamine (METH) abuse places a heavy burden on families and society. A growing amount of evidence has indicated communication between gut microbiota and the CNS in drug addiction, with associations to neural, endocrine and immune pathways. Thus, we searched for alterations in the gut microbiota and their potential effects in METH users through 16S rRNA gene sequencing. A decreased Shannon index indicated lower bacterial diversity in the METH users than in the age-match… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 63 publications
6
24
0
Order By: Relevance
“…To the best of our knowledge, the current study is the first to provide evidence for a link between altered fecal microbiota and systemic inflammation in MUD. Consistent with previous studies ( Cook et al., 2019 ; Yang Y. et al., 2021 ), our results demonstrated that subjects with MUD exhibited differences in the relative abundance of several microbial taxa. Importantly, the order Lactobacillales , containing several anti-inflammatory bacterial species, decreased in MUD and correlated positively with the plasma level of anti-inflammatory cytokine IL-10, as well as the duration of METH abstinence, suggesting a potential role of the gut-immune-brain axis ( Fung et al., 2017 ) in MUD.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…To the best of our knowledge, the current study is the first to provide evidence for a link between altered fecal microbiota and systemic inflammation in MUD. Consistent with previous studies ( Cook et al., 2019 ; Yang Y. et al., 2021 ), our results demonstrated that subjects with MUD exhibited differences in the relative abundance of several microbial taxa. Importantly, the order Lactobacillales , containing several anti-inflammatory bacterial species, decreased in MUD and correlated positively with the plasma level of anti-inflammatory cytokine IL-10, as well as the duration of METH abstinence, suggesting a potential role of the gut-immune-brain axis ( Fung et al., 2017 ) in MUD.…”
Section: Discussionsupporting
confidence: 92%
“…While the study cohort was comprised entirely of MSM, all of whom were engaging in anal intercourse, findings from this study might not generalize to the heterosexual population since it has been suggested that sexual behavior might influence the composition of gut microbiota ( Noguera-Julian et al., 2016 ). Another study involving 16 male methamphetamine abusers and 14 healthy subjects also reported alterations in gut microbiota diversity and composition associated with MUD ( Yang Y. et al., 2021 ). However, this study was limited by a relatively small sample size and inablility to adjust for possible confounders, highlighting the need for additional investigation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…SCFAs act as ligands for g-protein coupled receptors found throughout the body and the brain, histone deacetylase inhibitors which modify gene expression profiles, and influence inflammatory responses by reducing the recruitment and migration of immune cells (Jayasimhan and Marino, 2019; Kimura et al, 2011; Müller et al, 2019; van de Wouw et al, 2018; Fellows et al, 2018; Vinolo et al, 2011). Many studies, both preclinical and clinical have linked alterations of the microbiome to drugs of abuse, including opioids (Xiao et al, 2018; Hofford et al, 2019; Wang et al, 2018), cocaine (Cho and Blaser, 2012; Volpe et al, 2014; Kiraly et al, 2016a), alcohol (Engen et al, 2015; Leclercq et al, 2017; Leclercq et al, 2020) and psychostimulants (Simpson et al, 2021b; Cook et al, 2019; Yang et al, 2021). Previous studies have demonstrated increases in conditioned place preference (CPP) for cocaine (Kiraly et al, 2016b) and methamphetamine (Ning et al, 2017) was related to circulating SCFA levels and the microbes that produce them.…”
Section: Discussionmentioning
confidence: 99%
“…They also noted an increased concentration of Fusobacteria correlated to the duration of methamphetamine use and found higher concentrations of Bacteroides and Faecalibacterium, which have been correlated to persons with psychotic syndromes including schizophrenia and depression. 41 Zhao et al in 2019 aimed to find the cause of the mucosal inflammatory damage seen with methamphetamine use. Researchers theorized that the mechanism of inflammatory injury was due to Nod-like receptor protein 3 (NLRP3) inflammasome overexpression.…”
Section: Studies In the Literaturementioning
confidence: 99%